PENERAPAN BLENDED LEARNING MENGGUNAKAN MODEL FLIPPED CLASSROOM PADA PEMBELAJARAN FISIKA - Tri Ariani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
This study backgroud is incompleted average physics learning result of students’ class VII SMPN Air Satan. This study problem could be formulated “is science result of students class V SD Negeri Mataram after Blended Learning by using The Flipped Classroom model applied has completed significantly?”. The research method used pre-experimental design by one group pre-test and post-test category. Population and sample in this research were a whole of students’ class VII SMPN Air Satan consisting of 21 students or saturation sampling. Data collection technique was performed by using a test technique that amounts to 8 questions. Test data were analyzed with a z-test at a significant level a = 0.05 which zhitung (11.59) > ztabel (1.64) then Ho was rejected. Based on the post-test data analysis result could be concluded that physics learning result of students’ class V SD Negeri Mataram after Blended Learning by using The Flipped Classroom model applied has completed significantly. The average of physics learning result students’ class VII SMPN Air Satan after Blended Learning by using The Flipped Classroom model applied is 87.20 and the precentage of students total that completed reach 100%.